Preparation, spectral characterization, structural study, and evaluation of antibacterial activity of Schiff base complexes for VOII, CrIII, MnII, ZnII,CdII and CeIII (Baghdad Science Journal, 2015)
A new series of metal ions complexes of VO(II), Cr(III), Mn(II), Zn(II), Cd(II) and Ce(III) have been synthesized from the Schiff bases (4-chlorobenzylidene)-urea amine (L1) and (4-bromobenzylidene)-urea amine (L2). Structural features were obtained from their elemental microanalyses, magnetic susceptibility, molar conductance, FT-IR, UV–Vis, LC-Mass and 1HNMR spectral studies. The UV–Vis, magnetic susceptibility and molar conductance data of the complexes suggest a tetrahedral geometry around the central metal ion except, VOII complexes that has square pyramidal geometry, but CrIII and CeIII octahedral geometry. The biological activity for the ligand (L1) and its Vanadium and Cadmium complexes were studied. Structural geometries of compounds also were suggested in gas phase by using theoretical treatments, using Hyper Chem-6 program for the molecular mechanics and semi-empirical calculations. The heat of formation (?Hf ?) and binding energy (?Eb) in the temperature of 298K for the free ligand (L1) and their metal complexes were calculated by PM3 and ZINDO/I methods. The electrostatic potential of the free ligands were calculated to investigate the reactive sites of the molecules.Bacteriological evaluation of considerable number of these compounds were maintained using organisms Escherichia coli and Staphylococcus aureus,and they were found to exhibit the high effect of activity. This may be attributed to the impact of both the Schiff bases and the metal present in these complexes.